Garis panduan Pendekatan Syariah Terhadap Pengurusan Komisen Dana Awam Oleh Pertubuhan Bukan Kerajaan (NGOs) - Khadijah Amira Abdul Rashid; Mahyeddin Mohd Salleh; Mohd Soberi Awang (USIM Press, 2024)
Donation collection activity is one of the methods used by the NGOs to raise fund. The purpose of this researchis to study the management aspects of donation fund by NGOs,identify the factors that affect the determination of commission rate andpropose asyariah compliant guideline on the commission management of public donation. The methodology used is qualitative method by using document analysis and interview to the six NGOs. The findings show that there are several management aspects of donation fund applied by the NGO. There are four factors that affect the determination of commission rate which are wage of amil,decision of top management, guideline from mufti, zakahinstitution and other NGOs and according to the project and management cost. Moreover, seven guidelines according to the syariah are created on the commission management of public donation which are predominantly Muslim staff, managing the aspects of donation fund, applying the contract of ijarah, wakalahor ji’alah, take the commission between 12.5% to 20%,informing the commission taken to the donor, notifying the donation fund that has been channelled and donation fund are kept in syariah compliant bank. This guideline can be used as a reference to the other NGOs